Development of Geometry Flipbook Multimedia Learning Media for Elementary School students in Mattiro Bulu District, Pinrang Regency - Zaid Zainal; Abdul Halik; Muhammad Asrul Sultan; Asmirinda Resa (Universitas Negeri Makassar, 2021)
This study aims to develop a learning media in the form of multimedia geometry flipbook that are suitable for use by elementary school students. This research uses Research and Development Method, with The phases in this research consist of; (1) product analysis, (2) design products, (3) Development, validation and revision. This research used is a mixed approach. The results of the research at the analysis stage, the researcher found problems through a geometry ability test, analyzed the curriculum, and the students needs. The results of the design stage, namely designing the story board, preparing the content/material to be included in each menu, and compiling the learning media assessment instrument. The results of the development stage, namely product manufacture and validation and revision. The results of expert validation by material experts are included in the very worthy criteria (96.95%). The results of the validation by media experts showed very worthy criteria (98.18%). The results of the teacher's response as learning practitioners showed very worthy criteria (89.04%). Based on these results, the multimedia flipbook learning media for elementary school students in the Mattiro Bulu sub-district developed is suitable for learning geometry in elementary schools.